1998
DOI: 10.1016/s0370-2693(98)00201-9
|View full text |Cite
|
Sign up to set email alerts
|

Two pion correlations as a possible experimental probe for disoriented chiral condensates

Abstract: We discuss two-pion correlations as a possible experimental probe into disoriented chiral condensates. In particular, we point out that the iso-singlet squeezed states of the BCS type have peculiar two-particle correlations in the back-to-back and the identical momentum configurations which should be detectable experimentally. We motivate the examination of the squeezed state by showing that such state naturally appears in a final stage of nonequilibrium phase transitions via the parametric resonance mechanism… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 12 publications
0
29
0
Order By: Relevance
“…[13][14][15][16] The condensate moves periodically and the soft mode is enhanced by the motion of the condensate. The parametric resonance occurs if the temperature is approximately constant, because the condensate shows approximate periodic motion.…”
Section: -8mentioning
confidence: 99%
“…[13][14][15][16] The condensate moves periodically and the soft mode is enhanced by the motion of the condensate. The parametric resonance occurs if the temperature is approximately constant, because the condensate shows approximate periodic motion.…”
Section: -8mentioning
confidence: 99%
“…One can consider another situation, where a classical chiral condensate aligns in the σ direction and oscillates. In this case, it is shown that the parametric resonance mechanism works [8,9,10,11,12] and an isosinglet squeezed quantum state is derived dynamically [9]. The classical chiral condensate has isospin I = 0 because one has assumed that it aligns in the σ direction.…”
Section: Introductionmentioning
confidence: 99%
“…Pion measurements in individual collision events can distinguish DCC isospin fluctuations from a thermal background only if the disoriented region is sufficiently large [2]. DCC can then be the dominant source of pions at low transverse momenta, since p t ∼ 1/R for a coherent region of size R. Experiments focusing on low p t can study neutral and charged pion fluctuations [19], wavelet [23] and HBT signals [2,24] to extract detailed information. In contrast, for small domains (R < 3 fm [2]) DCC signals are hidden by fluctuations due to ordinary incoherent production mechanisms.…”
Section: Introductionmentioning
confidence: 99%